Maternal β-Hemolytic Streptococcal Pharyngeal Exposure and Colonization in Pregnancy - Giv Heidari-Bateni; Anoop K. Brar; Matthew Hall; Trupti Hathcock; Deirdre Epstein; Lisa S. Goessling; Madeleine W. Cunningham; Pirooz Eghtesady (Hindawi Limited, 2014)
Objectives. To report the pharyngeal colonization rate of β-hemolytic streptococci and changes in the value of antistreptolysin O (ASO) and anti-DNase B serology titers during pregnancy. Methods. Healthy pregnant women were recruited and blood was drawn in each trimester. The upper limit of normal (ULN) values for ASO and anti-DNase B was calculated for each trimester. Throat swabs were collected for culture and positive cultures were further assessed for the identification of serogroup of the isolated β-hemolytic streptococcus. Results. Out of a total of 126 pregnant women, 34.1% had positive throat cultures. Group C and group G strains were isolated in 18.2% of throat cultures while group F was detected in 13.5% of cases. The rate of colonization with GAS was 1.6%. There was an overall drop in ASO titer during pregnancy while anti-DNase B titers remained relatively unchanged. ULN values of 164IU, 157IU, and 156IU were calculated for ASO at the first, second, and third trimesters, respectively. Based on the ULN values, 28.6% of patients had recent streptococcal exposure. Conclusions. These results show that pregnant women act as a reservoir for spreading potentially immunogenic (groups C and G) and disease producing (group F) virulent strains of streptococci.